TaF5 catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg24Y5 type hydrogen storage alloy and preparation method thereof
Through TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg24Y5 hydrogen storage alloy, multi-component rare earths and transition metal elements are added, combined with mechanical method and ball milling technology to form a nanocrystalline structure, solving the problems of insufficient thermal stability and hydrogen absorption and release performance of existing hydrogen storage alloy materials, and achieving efficient hydrogen storage and release performance.
Patent Information
- Application Number
- CN202510483061.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-08-01
- Estimated Expiration
- 2045-04-17
AI Technical Summary
The existing hydrogen storage alloy materials have shortcomings in thermal stability, thermal and dynamic properties of hydrogen absorption and discharge, and it is difficult to meet the requirements of high energy density and high safety.
A high-capacity RE-Mg-Ni-Cu-Be-based Mg24Y5 hydrogen storage alloy catalyzed by TaF5 is used to add multi-component rare earth elements Y and Ce and transition group metal elements Ni, Cu and Be, combined with mechanical method to crush the fast-quenching alloy sheet and mechanical ball mill for appropriate time, and the catalyst TaF5 is added to form nanocrystal structure and high-density crystal defects, improving the hydrogen absorption and discharge performance.
It achieves high capacity hydrogen absorption and discharge performance, has excellent hydrogen absorption and discharge thermodynamics and kinetics, and is suitable for hydrogen fuel cell hydrogen supply carrier field, and the preparation process is simple and easy to operate.
Smart Images

Figure CN120400658A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid hydrogen storage alloy materials, and in particular to a TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg 24 Y5-type hydrogen storage alloy and a preparation method thereof. Background Art
[0002] In recent decades, hydrogen, as a clean energy source, the most abundant element in the universe, the lightest fuel, and the most ideal energy carrier with the richest energy per unit mass, has attracted worldwide interest. Safe and efficient hydrogen storage methods are key technologies for promoting hydrogen and fuel cell power technologies in transportation, stationary, and portable applications. Traditional physical methods, such as compression or liquefaction, have inherent problems of low volumetric energy density, high economic cost, and poor safety. Another option is chemical hydrogen storage in hydrogen-rich liquids and solids, which may achieve high energy storage density. Examples of such solid materials and liquids include boron-based compounds such as LiBH4, NaBH4, and NH3BH3, and organic liquids such as cyclohexane and decalin. However, the irreversible nature of these hydrogen storages means it is not a viable hydrogen storage method. Physical hydrogen storage research on carbon materials such as activated carbon, carbon nanotubes, graphene, and carbon nanofibers is also an active research field. However, the hydrogen storage capacity of these carbon materials completely depends on the external hydrogen pressure and temperature.
[0003] Metal hydrides are considered a promising hydrogen storage material due to their high energy density and high safety. It is a solid-state hydrogen storage method that can reversibly absorb hydrogen in atomic form without the need for high pressure (generally below 3 MPa) and chemically compress hydrogen to a higher storage density. For example, a typical LaNi5-based hydride can reversibly absorb and release about 0.9 wt.% of hydrogen at 100 °C. The TiFe alloy has a high hydrogen storage capacity (about 2 wt.%), however, its activation process is harsh and the absorption / desorption kinetics are poor. MgH2 has the highest energy density among all reversible metal hydrides available for hydrogen storage. MgH2 meets many technical requirements, such as light weight, low cost, and a relatively large weight hydrogen storage capacity (7.6 wt.%), however, its hydrogenation / dehydrogenation kinetics are slow, the reaction temperature is high, and it cannot meet the requirements of on-vehicle hydrogen supply equipment; although the performance is optimized by alloying with transition metals, adding rare earths and nickel, etc., the reaction temperature is still high, the reversible hydrogen capacity needs to be further improved, the hydrogenation / dehydrogenation kinetics are still not ideal under certain conditions, and some improvement methods may lead to problems such as increased cost or decreased material stability. Summary of the Invention
[0004] In view of the above analysis, embodiments of the present invention aim to provide a TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg24 Y5 type hydrogen storage alloy and its preparation method, which are used to solve at least one of the problems such as high thermal stability of existing alloy hydrides and poor thermodynamic and kinetic properties of alloy hydrogen absorption and desorption.
[0005] On the one hand, an embodiment of the present invention provides a TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg 24 Y5 type hydrogen storage alloy, and the chemical formula composition of the hydrogen storage alloy is: Mg 25 Y 5-x Ce x Ni 2-y-z Cu y Be z +m wt.%TaF5, where x, y, z are atomic ratios, 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 0.5, and m is the percentage of TaF5 in Mg 25 Y 5-x Ce x Ni 2-y-z Cu y Be z alloy, 3 ≤ m ≤ 10.
[0006] Preferably, x:y:z = 1:0.5:0.3, m = 8.
[0007] On the other hand, an embodiment of the present invention also provides a preparation method of a TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg 24 Y5 type hydrogen storage alloy, which is used for the preparation of the hydrogen storage alloy, and includes the following steps:
[0008] S1. Weigh the raw materials according to the preset chemical formula composition, and increase a certain proportion of burn loss when weighing Mg and rare earths Y and Ce;
[0009] S2. Place the prepared raw materials in a magnesia crucible in sequence, evacuate and then fill with a protective gas and heat to obtain a molten liquid master alloy;
[0010] S3. After maintaining the liquid master alloy prepared in S2 in a protective gas atmosphere for 3 to 5 minutes, inject it into a tundish with a BN nozzle embedded at the bottom, and the liquid alloy continuously sprays onto the smooth surface of a rotating water-cooled copper roller through the slit of the BN nozzle at the bottom of the tundish to obtain a rapidly quenched alloy ribbon;
[0011] S4. Mechanically crush and screen the rapidly quenched alloy ribbon to obtain alloy powder, put the sieved alloy powder, a certain amount of TaF5 catalyst and stainless steel grinding balls into a stainless steel ball milling tank, evacuate and then fill with high-purity argon gas, and ball mill in an all-round planetary high-energy ball mill to obtain ball-milled alloy powder, that is, the hydrogen storage alloy.
[0012] Specifically, the mass percentage of the burned-off amount of Mg in S1 is 8%-10%, and the mass percentage of the burned-off amount of the rare earth Y and Ce is 5%-7%.
[0013] Furthermore, the specific process and parameters in S2 are: vacuuming to 1×10 -2 ~5×10 -5 Pa, introduce 0.01-0.1MPa high-purity helium or a helium + argon mixture with a volume ratio of 1:1 as a protective gas, and heat to 1450-1600℃.
[0014] Preferably, the nozzle slit width of the NB nozzle in S3 is 0.295-0.305 mm, and the linear speed of the water-cooled copper roller is 2-30 m / s.
[0015] Specifically, the thickness of the rapidly quenched alloy strip in S3 is between 100-450 μm.
[0016] Exemplarily, the rapidly quenched alloy ribbon has a nanocrystalline structure with a grain size of 10-100 nm.
[0017] Furthermore, the specific parameters of the ball milling process in S4 are: ball-to-material ratio 20:1, ball mill speed 350 rpm, and ball milling time 2 to 7 hours.
[0018] Specifically, the ratio of nanocrystals to amorphous phases in the ball-milled alloy powder obtained in S4 ranges from 76:1 to 83:1.
[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0020] 1. The present invention reduces the stability of Mg-based hydride and improves its hydrogen absorption and desorption kinetics by adding multiple rare earth elements Y and Ce and transition metal elements Ni, Cu and Be;
[0021] On the one hand, the addition of metal elements Ni, Cu and Be promotes the dissociation of hydrogen and reduces the bonding strength of Mg-H bond; on the other hand, by adding a small amount of multi-element rare earth Y and Ce, and adding a small amount of metal elements Ni, Cu and Be for alloying, Mg and Y can form the main phase Mg of the alloy. 24 Y5, Ce and Mg can form CeMg 12 Phase, Mg and Ni can form Mg2Ni phase, Cu and Be can form CuBe phase and other intermetallic compounds; Mg2Ni itself is a hydrogen absorbing phase, and although CuBe cannot absorb hydrogen, it has a positive effect on the absorption and desorption of hydrogen in Mg-based alloys; rare earth Y and Ce and metal Be can form highly stable YH2 / YH3 and CeH with hydrogen. 2.73The hydrides such as BeH2 can significantly reduce the stability of magnesium hydride, and these hydrides are distributed as dispersed particles in the alloy matrix, which are the nuclei for the nucleation of magnesium hydride and have an obvious catalytic effect on the hydrogen absorption and desorption processes of Mg-based alloys.
[0022] 3. The present invention uses a mechanical method to crush the rapidly quenched alloy flakes, adds a small amount of catalyst TaF5 and performs mechanical ball milling for an appropriate time. While maintaining the nanocrystalline microstructure of the rapidly quenched alloy, it can promote the introduction of high-density crystal defects and the improvement of the surface activity of the milled particles, improve the hydrogen storage performance of the target alloy, and further improve the hydrogen absorption and desorption thermodynamics and kinetics of the alloy.
[0023] On the one hand, the catalytic effect of TaF5 lies in its high hardness, which has an obvious cutting effect on the alloy particles during ball milling, improving the ball milling efficiency and making the particles of the ball-milled alloy finer. On the other hand, after adding a highly stable catalyst and ball milling, the catalyst can be evenly distributed between the alloy particles, forming a large number of active interfaces between the alloy and the catalyst. Such interfaces provide good nucleation sites for the formation and decomposition of hydrides.
[0024] 4. By adding a catalyst and selecting an appropriate ball milling time, the ball-milled alloy particles obtained in the present invention are approximately spherical, ensuring that there is no excessive amorphous phase in the ball-milled alloy, and ensuring good dispersion of the alloy powder without serious agglomeration, thereby ensuring that the hydrogen absorption capacity of the alloy does not decrease significantly.
[0025] 5. The hydrogen storage alloy powder prepared in the present invention has excellent hydrogen absorption and desorption capacities and good hydrogen absorption and desorption thermodynamics and kinetics. The saturated hydrogen absorption amount at an initial hydrogen pressure of 3 MPa and 200 °C is ≥5.29%, the hydrogen absorption amount within 5 minutes at an initial hydrogen pressure of 3 MPa and 200 °C is ≥5.17%, and the hydrogen desorption amount within 20 minutes at an initial pressure of 1×10 -4 MPa and 270 °C is ≥4.79%. It shows extremely high application potential in the field of hydrogen fuel cell hydrogen supply carriers; and the preparation process of the alloy is simple and easy to operate, fully meeting the requirements of large-scale preparation.
[0026] In the present invention, the above technical solutions can also be combined with each other to achieve more preferred combination schemes. Other features and advantages of the present invention will be described in the subsequent specification, and some advantages can be made obvious from the specification or understood by implementing the present invention. The objectives and other advantages of the present invention can be realized and obtained through the content specifically pointed out in the specification and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings are only for the purpose of showing specific embodiments and are not considered as limiting the present invention. Throughout the drawings, the same reference signs represent the same components.
[0028] Figure 1 The SEM morphologies of the cast alloys of Examples 1 to 6 of the present invention are shown;
[0029] FIG2( a ) is a photograph of the rapidly quenched alloy ribbon of Example 1 of the present invention;
[0030] FIG2( b ) is the HRTEM morphology of the microstructure of the rapidly quenched alloy ribbon of Example 1 of the present invention;
[0031] Figure 3 The SEM morphologies of the ball-milled alloys of Examples 1 to 6 of the present invention are shown;
[0032] Figure 4 XRD diffraction spectra of the ball-milled powders of Examples 1 to 6 of the present invention;
[0033] Figure 5 HRTEM morphologies of the ball-milled powders of Examples 1 to 6 of the present invention. DETAILED DESCRIPTION
[0034] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, and are not used to limit the scope of the present invention.
[0035] On the one hand, a specific embodiment of the present invention discloses a high capacity RE-Mg-Ni-Cu-Be based Mg 2+ catalyst catalyzed by TaF5. 24 Y5 type hydrogen storage alloy, its chemical formula is: Mg 25 Y 5-x Ce x Ni 2-y-z Cu y Be z +m wt.%TaF5, where x, y, z are atomic ratios, 0 <x≤2,0<y≤1,0<z≤0.5,m为TaF5占Mg 25 Y 5-x Ce x Ni 2-y-z Cu y Be z The percentage of the alloy, 3≤m≤10.
[0036] It should be noted that the high capacity RE-Mg-Ni-Cu-Be based Mg catalyzed by TaF5 24 The preparation method of Y5 type hydrogen storage alloy is as follows: the ingredients are prepared according to a preset chemical formula, heated and melted into a master alloy under gas protection, prepared into a thin strip by rapid quenching, mechanically crushed and sieved to obtain alloy powder, and then ball-milled with TaF5 catalyst and stainless steel grinding balls under argon protection for 2 to 7 hours to finally obtain a ball-milled hydrogen storage alloy.
[0037] Preferably, x:y:z = 1:0.5:0.3 and m = 8.
[0038] Optimize the design of the hydrogen storage alloy composition, make full use of the comprehensive characteristics of rare earth elements and ferromagnetic elements to improve the hydrogen storage performance of the alloy material; control the addition amount of the catalyst to avoid agglomeration during the subsequent ball milling process, which affects the hydrogen storage performance of the alloy. The specific functions are as follows:
[0039] Add a small amount of multi-component rare earth Y and Ce, and at the same time add a small amount of metal elements Ni, Cu and Be for alloying. Mg and Y can form the main phase Mg 24 Y5, Ce and Mg can form CeMg 12 phase, Mg and Ni can form Mg2Ni phase, Cu and Be can form intermetallic compounds such as CuBe phase; among them, Mg2Ni itself is a hydrogen absorption phase, and although CuBe cannot absorb hydrogen, it has a positive effect on the hydrogen absorption and desorption of Mg-based alloys;
[0040] Rare earth Y and Ce and metal Be can form hydrogen nanocrystalline phases with very high thermal stability such as YH2 / YH3, CeH 2.73 and BeH2. A large number of nanocrystalline stable phases play a pinning role during the hydrogen absorption and desorption process, making the magnesium matrix phase nanocrystallized and introducing more nanocrystalline interfaces, providing more channels for hydrogen diffusion. Moreover, these hydrides are diffusely distributed in the alloy matrix and are the nucleation sites for the hydrogen absorption and desorption reaction, which has an obvious catalytic effect on the hydrogen absorption and desorption process of Mg-based alloys.
[0041] On the other hand, a specific embodiment of the present invention also discloses a preparation method of a TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg 24 Y5 type hydrogen storage alloy, comprising the following steps:
[0042] S1. Weigh the materials according to the preset chemical formula composition, and increase a certain proportion of burn loss when weighing Mg and rare earths Y and Ce;
[0043] S2. Place the prepared raw materials in a magnesia crucible in sequence, evacuate and then fill with a protective gas and heat to obtain a molten liquid master alloy;
[0044] S3. After keeping the liquid master alloy prepared in S2 in a protective gas atmosphere for 3 - 5 minutes, inject it into a tundish with a BN nozzle embedded at the bottom, and the liquid alloy continuously sprays onto the smooth surface of a rotating water-cooled copper roller through the slit of the BN nozzle at the bottom of the tundish to obtain a rapidly quenched alloy thin strip with a thickness between 100 - 450 μm;
[0045] S4. Mechanically crush the rapidly quenched alloy ribbon and screen it to obtain alloy powder. Put the screened alloy powder, a certain amount of TaF5 catalyst, and stainless steel grinding balls into a stainless steel ball milling tank. After evacuating, fill it with high-purity argon gas and ball mill it in an all-round planetary high-energy ball mill to obtain the ball-milled alloy powder, which is the hydrogen storage alloy.
[0046] Rapid quenching treatment of the liquid master alloy can obtain a precursor with ultrafine grains (nanoscale). The rapidly quenched alloy has a columnar crystal structure, which is a uniform nanocrystalline structure. Its grain boundaries provide good channels for the diffusion of hydrogen atoms, which is particularly beneficial for improving the hydrogen absorption and desorption kinetics of Mg-based alloys. In addition, the rapidly quenched alloy structure contains a high density of crystal defects, including dislocations, stacking faults, twins, a large number of grain boundaries, etc. This microstructure is extremely beneficial for improving the thermodynamic and kinetic properties of the alloy. Different from the crystal defects formed by mechanical ball milling after casting the master alloy ingot, the ultrafine structure and crystal defects obtained by rapid quenching have high stability, and the grains are not easy to aggregate and grow after multiple hydrogen absorption and desorption cycles. In terms of hydrogen absorption and desorption performance, it not only has excellent hydrogen absorption and desorption kinetics but also has good cycle stability.
[0047] After mechanically crushing the rapidly quenched alloy flakes, adding the catalyst TaF5, and ball milling for a short time, while maintaining the microstructure of the rapidly quenched alloy, the surface state of the alloy is improved, and the advantages of the two preparation processes are exerted. The catalyst is evenly distributed in the alloy matrix during the ball milling process, and its catalytic effect can be fully exerted, thereby improving the hydrogen absorption and desorption thermodynamics and kinetics of the alloy. On the one hand, the catalytic effect of TaF5 lies in its high hardness, which has an obvious cutting effect on the alloy particles during the ball milling process, making the particles of the ball-milled alloy finer. On the other hand, after adding a highly stable catalyst and ball milling, the catalyst can be evenly distributed between the alloy particles, forming a large number of active interfaces between the alloy and the catalyst. This interface provides good nucleation sites for the formation and decomposition of hydrides. It is precisely due to the combination of rapid quenching, ball milling, and adding a catalyst that the hydrogen absorption and desorption thermodynamics and kinetics of the alloy are greatly improved.
[0048] Preferably, the mass percentage of the burn loss of Mg in S1 is 8%-10%, and the mass percentage of the burn loss of rare earths Y and Ce is 5%-7%. Mg and rare earths Y and Ce are easy to volatilize and will cause certain losses during the batching and heating and melting processes, so a certain amount of burn loss needs to be added.
[0049] Specifically, the specific process and parameters in S2 are: evacuate to 1×10 -2 ~5×10 -5Pa, introduce high-purity helium gas at 0.01 - 0.1 MPa or a helium + argon mixed gas with a volume ratio of 1:1 as the protective gas, heat to 1450 - 1600 °C, and the heating method is arc melting or induction heating melting.
[0050] It should be noted that the order of placing the raw materials in the magnesium oxide crucible in S2 is as follows: blocky rare earths Y and Ce are placed at the bottom of the crucible, electrolytic Ni is placed above rare earths Y and Ce, metallic Cu and Be are placed above metallic Ni, and blocky metallic Mg is placed on the top. This placement order is determined according to the melting points and solid solubilities of the metals, which can cause the metals to melt in sequence from the lowest melting point to the highest, effectively reducing the burning loss of elements such as Y and Ce, making the alloy composition more stable and the element distribution more uniform.
[0051] Exemplarily, in S3, the nozzle slit width of the NB nozzle is set to 0.295 - 0.305 mm, and the linear speed of the water-cooled copper roller rotation is 2 - 30 m / s. Specifically, the linear speeds are 2 m / s, 5 m / s, 8 m / s, 10 m / s, 15 m / s, 18 m / s, 20 m / s, 22 m / s, 25 m / s, 28 m / s, 30 m / s; by controlling the copper roller rotation speed, a suitable rapid quenching cooling rate is determined to ensure that the rapidly quenched alloy ribbon has a nanocrystalline structure of more than 98.5%, and the grain size is 10 - 100 nm.
[0052] The rapid quenching treatment of the liquid master alloy needs to ensure that the rapidly quenched alloy ribbon has as many nanocrystalline structures as possible. If the rapid quenching cooling rate is too fast, a considerable proportion of amorphous phase will appear in the structure, resulting in a significant decrease in the hydrogen absorption capacity of the alloy; if the cooling rate is too slow, a relatively large number of microcrystalline structures will appear, weakening the hydrogen absorption and desorption kinetic performance of the alloy.
[0053] Preferably, the linear speed of the water-cooled copper roller rotation is 20 m / s.
[0054] Preferably, after the rapidly quenched alloy ribbon is mechanically crushed in S4, the sieving operation uses a 200-mesh sieve; before the catalyst is added to the stainless steel ball milling tank, it is ground and then passed through a 200-mesh sieve.
[0055] Specifically, the specific parameters of the ball milling process in S4 are: the ball-to-material ratio is 20:1, the rotation speed of the ball mill is 350 revolutions per minute, and the ball milling time is 2 - 7 hours. Specifically, the ball milling times are 2, 3, 4, 5, 6, 7 hours; preferably, the ball milling time is 6 hours.
[0056] During the ball milling process, the ball mill stops for 0.5 hours every 1 hour of continuous operation to prevent the temperature of the ball milling tank and abrasive from being too high. The determination of the ball milling time is crucial and has a great impact on the combination of the alloy and the catalyst. On the one hand, if the ball milling time is too long, a large amount of amorphous phase will appear, resulting in a decrease in the hydrogen storage performance of the alloy; the optimal ball milling time can ensure that there is no excessive amorphous phase in the ball milled alloy, and the volume ratio range of nanocrystals to amorphous phase in the ball milled alloy powder is 76:1 to 83:1. Preferably, the volume ratio of nanocrystals to amorphous phase is 80:1. On the other hand, an appropriate ball milling time can ensure good dispersion of the alloy powder without serious agglomeration, thus ensuring that the hydrogen absorption capacity of the alloy does not decrease significantly. An overly long ball milling time will result in more amorphous phase in the microstructure, and at the same time, due to cold welding between particles, agglomeration will occur, which all lead to a decrease in the hydrogen absorption and desorption performance of the alloy.
[0057] In summary, the present invention reduces the stability of Mg-based hydrides and improves their hydrogen absorption and desorption kinetic properties by adding multi-element rare earth elements Y and Ce and transition metal elements Ni, Cu, and Be; uses mechanical crushing of rapidly quenched alloy flakes, adds a small amount of catalyst TaF5 and performs mechanical ball milling for an appropriate time to further improve the hydrogen absorption and desorption thermodynamics and kinetics of the alloy; the hydrogen storage alloy powder prepared by the present invention has excellent hydrogen absorption and desorption capacity and good hydrogen absorption and desorption thermodynamics and kinetics, showing extremely high application potential in the field of hydrogen fuel cell hydrogen supply carriers; and the preparation process of the alloy is simple and easy to operate, fully meeting the requirements of large-scale preparation.
[0058] The following specifically describes the TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg 24 Y5-type hydrogen storage alloy and its preparation method of the present invention.
[0059] Examples 1 to 6 are all prepared for the TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg 24 Y5-type hydrogen storage alloy by the following method:
[0060] S1. Select bulk metals Mg, rare earth metals Y and Ce, electrolytic Ni, metal Cu, and Be according to the chemical formula composition of each example. The metal purity requirement is ≥99.5%. After grinding the selected bulk metals to remove the surface oxide layer, weigh them according to the chemical dosage ratio; among them, metal Mg is increased by 8% and rare earth Y and Ce are increased by 5% in the ratio to make up for the loss during melting.
[0061] S2. Place the prepared raw materials in a magnesia crucible in sequence, evacuate and then fill with a protective gas and perform induction heating to obtain a molten liquid master alloy.
[0062] Process parameters during the heating process: Evacuate to 1×10-2 ~5×10 -4 Pa, fill with high-purity helium gas with a filling pressure of 0.01 - 0.1 MPa or a helium + argon mixed gas with a volume ratio of 1:1; the melting temperature is 1450 - 1600 °C;
[0063] S3. After maintaining the liquid master alloy prepared in S2 for 3 - 5 minutes under a protective gas atmosphere, inject it into a tundish with a BN nozzle embedded at the bottom. The liquid alloy continuously sprays onto the smooth surface of a rotating water-cooled copper roll through the slit of the BN nozzle at the bottom of the tundish. The surface linear velocity of the water-cooled copper roll is 2 - 30 m / s to obtain a rapidly quenched alloy thin strip with a thickness between 100 - 450 μm;
[0064] S4. After mechanically crushing the rapidly quenched thin sheet and passing it through a 200-mesh sieve, mix it with the catalyst TaF5 and stainless steel grinding balls and load them into a stainless steel ball mill jar. Ball mill for 2 - 7 hours using an all-round planetary ball mill. The ball mill stops for 0.5 hours every 1 hour of continuous operation to obtain the ball-milled alloy powder, which is the hydrogen storage alloy.
[0065] S5. Structure analysis and performance testing: Use XRD to test the phase structure of the as-cast and ball-milled powders, use high-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM) to observe the morphology and microstructure of the as-cast and ball-milled alloys, and use selected area electron diffraction (SAED) to determine the crystal state of the alloy;
[0066] Use a semi-automatic Sieverts device to test the hydrogen absorption activation performance, hydrogen storage capacity, and hydrogen absorption and desorption kinetics of the alloy powder: among them, the hydrogen absorption temperature is 200 °C, and the initial hydrogen pressure is 3 MPa; the desorption temperature is 270 °C, and the desorption is carried out under a pressure of 1×10 -4 MPa.
[0067] The chemical composition and ratio of the specific embodiments of the present invention are selected as follows:
[0068] Example 1: Mg 25 Y4Ce1Ni 1.2 Cu 0.5 Be 0.3 +8 wt.% TaF5
[0069] Example 2: Mg 25 Y3Ce2Ni 1.2 Cu 0.5 Be 0.3 +8 wt.% TaF5
[0070] Example 3: Mg 25 Y4Ce1Ni 0.7 Cu1Be 0.3 +3wt.% TaF5
[0071] Example 4: Mg 25 Y4Ce1Ni1Cu 0.5 Be 0.5 + 5 wt.% TaF5
[0072] Example 5: Mg 25 Y4Ce1Ni 1.2 Cu 0.5 Be 0.3 + 9 wt.% TaF5
[0073] Example 6: Mg 25 Y4Ce1Ni 1.2 Cu 0.5 Be 0.3 + 10 wt.% TaF5
[0074] Comparative Example 1: Mg 24 Y5 (rapid quenching + ball milling)
[0075] Comparative Example 2: Mg 25 Y4Ce1Ni 1.2 Cu 0.5 Be 0.3 (rapid quenching + ball milling)
[0076] Comparative Example 3: Mg 25 Y4Ce1Ni 1.2 Cu 0.5 Be 0.3 + 3 wt.% TaF5 (for 10 hours)
[0077] Comparative Example 4: Mg 25 Y4Ce1Ni 1.2 Cu 0.5 Be 0.3 + 8 wt.% TaF5 (for 10 hours)
[0078] Process technical parameters of Example 1:
[0079] S1. According to the chemical formula Mg 25 Y4Ce1Ni 1.2 Cu 0.5 Be 0.3 , select massive Mg, rare earths Y and Ce, electrolytic Ni, metal Cu and Be. The metal purity is 99.5%. Weigh according to the stoichiometric ratio. Charge 5 kg per furnace. Among them, massive metal Mg is 2715.6 g, rare earth Y is 1545.2 g, rare earth Ce is 608.8 g, electrolytic Ni is 291.5 g, metal Cu is 131.5 g, and metal Be is 11.2 g.
[0080] S2. Place the weighed bulk metal in a magnesia crucible of an intermediate frequency induction furnace according to the designed process. Place the bulk rare earths Y and Ce at the bottom of the crucible, electrolytic Ni on top of the rare earths Y and Ce, metal Cu and Be on top of the electrolytic Ni, and bulk metal Mg on the top. Then cover the furnace lid, evacuate for 30 minutes until the vacuum degree reaches above 5×10 -2 Pa, and then fill with high-purity helium protective gas until the air pressure reaches 0.04 MPa. Adjust the power to 5 kW and control the temperature at 650 °C to melt the metal Mg. Then adjust the power to 25 kW and control the temperature at 1600 °C to melt the remaining metals.
[0081] S3. After the molten alloy is held for 5 minutes under a protective gas atmosphere, directly inject the liquid master alloy into a tundish with an NB nozzle embedded at the bottom. The liquid alloy continuously drops from the gap of the NB nozzle at the bottom of the tundish (the nozzle gap width is 0.3 mm) onto the surface of a water-cooled copper roller rotating at a linear velocity of 20 m / s, obtaining a rapidly quenched alloy thin sheet with a thickness of 130 μm and an average grain size of 32 nm.
[0082] S4. Mechanically crush the rapidly quenched Mg 25 Y4Ce1Ni 1.2 Cu 0.5 Be 0.3 alloy thin sheet and pass it through a 200-mesh sieve. Weigh 20 grams of the sieved alloy powder, 1.6 grams of catalyst TaF5, and 400 grams of stainless steel grinding balls, and mix them together and load them into a 250-ml stainless steel ball milling jar. Evacuate and fill with high-purity argon gas and then seal. Ball mill in an all-round planetary high-energy ball mill for 6 hours, and the ball mill stops for 0.5 hours every 1 hour of continuous operation.
[0083] The raw materials of Examples 2 to 6 are weighed according to the chemical formula, and other preparation process parameters are the same as those of Example 1.
[0084] The raw materials of Comparative Examples 1 to 4 are weighed according to the chemical formula, and other preparation process parameters are basically the same as those of Example 1. The difference is that no catalyst is added during ball milling in Comparative Examples 1 and 2, different contents of catalysts are added in Comparative Example 3, and the ball milling duration in Comparative Examples 3 and 4 is 10 hours.
[0085] Figure 1 is the SEM morphology of the as-cast alloys of Examples 1 to 6. The results show that after adding multi-component rare earths and multi-metal alloying, a variety of intermetallic compounds are formed. Among them, Mg and Y form the Mg 24 Y5 main phase, Ce and Mg form the CeMg 12 phase, Mg and Ni form Mg2Ni, and Cu and Be form CuBe and other intermetallic compounds.
[0086] Figure 2(a) is a physical photo of the rapidly quenched alloy ribbon, and the thickness of the tested ribbon is 130 μm; as shown in Figure 2(b), it is found by HRTEM observation that the rapidly quenched alloy ribbon is almost completely nanocrystalline structure, and the average grain size is 32 nm.
[0087] Figure 3 SEM morphologies of the ball-milled powders of Examples 1-6 are shown. It is observed that after ball milling, the alloy particles have good dispersion and no obvious agglomeration phenomenon is formed.
[0088] Figure 4 XRD patterns of the ball-milled alloys of Examples 1-6 are shown. It is found that the ball-milled materials have the structural characteristics of nanocrystals and amorphous. Ball milling makes the diffraction peaks of the alloy significantly broadened, which is the result of grain refinement and increased lattice internal stress caused by ball milling.
[0089] Figure 5 HRTEM morphologies of the ball-milled alloys of Examples 1-6 are shown, indicating that the alloys have nanocrystalline and very small amounts of amorphous structures.
[0090] The gaseous hydrogen absorption and desorption amounts and kinetics of the alloy powders of the examples and comparative examples were tested using a fully automatic Sieverts apparatus, and the results are shown in Table 1.
[0091] Table 1 Hydrogen absorption and desorption kinetics of alloy powders with different compositions
[0092]
[0093] C max —Saturated hydrogen absorption amount (wt.%) at an initial hydrogen pressure of 3 MPa and 200 °C; —Hydrogen absorption amount (wt.%) within 5 minutes at an initial hydrogen pressure of 3 MPa and 200 °C, —Hydrogen desorption amount (wt.%) within 20 minutes at an initial pressure of 1×10 -4 MPa and 270 °C.
[0094] The above results show that the ball-milled alloy powders of the present invention have high hydrogen absorption and desorption capacities and excellent kinetic properties. In particular, the alloy has good hydrogen desorption performance at a relatively low temperature (270 °C).
[0095] Compared with the examples, in Comparative Example 1, the alloy composition does not meet the requirements of the present invention, and no catalyst is added during the ball milling process, and its hydrogen storage capacity and hydrogen absorption and desorption kinetic properties are much lower than those of the examples; compared with Example 1, in Comparative Example 2, the alloy composition is the same, but no catalyst is added during the ball milling process, and its hydrogen storage capacity and hydrogen absorption and desorption kinetic properties are lower than those of Example 1.
[0096] Compared with the embodiment, the alloy composition and catalyst addition amount of Comparative Examples 3 and 4 meet the requirements of the present invention, but the ball milling time is too long, resulting in a decrease in the hydrogen absorption and desorption kinetics.
[0097] In summary, the present invention reduces the stability of Mg-based hydrides and improves their hydrogen absorption and desorption kinetics by adding multi-element rare earth elements Y and Ce and transition metal elements Ni, Cu and Be; mechanically crushes rapidly quenched alloy flakes, adds a small amount of catalyst TaF5 and applies mechanical ball milling for an appropriate time, so that the hydrogen absorption and desorption thermodynamics and kinetics of the alloy are further improved; the hydrogen storage alloy powder prepared by the present invention has excellent hydrogen absorption and desorption capacity and good hydrogen absorption and desorption thermodynamics and kinetics, and shows extremely high application potential in the field of hydrogen supply carriers for hydrogen fuel cells; and the preparation process of the alloy is simple and easy to operate, which can fully meet the requirements of large-scale preparation.
[0098] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with this technical field within the technical scope disclosed by the present invention should be covered by the scope of protection of the present invention.
Claims
1. A TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg 24 Y5-type hydrogen storage alloy, characterized in that The chemical formula composition of the hydrogen storage alloy is: Mg 25 Y 5-x Ce x Ni 2-y-z Cu y Be z + mwt.% TaF5, where x, y, z are atomic ratios, 0 < x ≤ 2, 0 < y ≤ 1, 0 < z ≤ 0.5, and m is the percentage of TaF5 in the Mg 25 Y 5-x Ce x Ni 2-y-z Cu y Be z alloy, 3 ≤ m ≤ 10.
2. The hydrogen storage alloy according to claim 1, wherein x:y:z = 1:0.5:0.3, m = 8.
3. A preparation method of a TaF5-catalyzed high-capacity RE-Mg-Ni-Cu-Be-based Mg 24 Y5-type hydrogen storage alloy, characterized in that, The preparation of the hydrogen storage alloy according to claim 1 or 2 comprises the following steps: S1. Weigh the ingredients according to a preset chemical formula composition, with a certain proportion of loss on ignition added when weighing Mg and rare earths Y and Ce; S2. Place the prepared raw materials in a magnesia crucible in sequence, evacuate the air, then fill with a protective gas and heat to obtain a molten liquid master alloy; S3. After maintaining the liquid master alloy prepared in S2 in a protective gas atmosphere for 3 - 5 minutes, pour it into a tundish with a BN nozzle embedded at the bottom, and continuously spray the liquid alloy through the slit of the BN nozzle at the bottom of the tundish onto the smooth surface of a rotating water-cooled copper roller to obtain a rapidly quenched alloy ribbon; S4. Mechanically crush and screen the rapidly quenched alloy ribbon to obtain alloy powder, put the sieved alloy powder, a certain amount of TaF5 catalyst and stainless steel grinding balls into a stainless steel ball milling tank, evacuate the air and then fill with high-purity argon, and ball mill in an all-round planetary high-energy ball mill to obtain ball-milled alloy powder, i.e., the hydrogen storage alloy.
4. The preparation method according to claim 3, characterized in that, The mass percentage of the loss on ignition of Mg in S1 is 8% - 10%, and the mass percentage of the loss on ignition of rare earths Y and Ce is 5% - 7%.
5. The preparation method according to claim 3, wherein The specific process and parameters in S2 are as follows: evacuate to 1×10 -2 ~5×10 -5 Pa, introduce high-purity helium gas at 0.01~0.1MPa or a helium + argon mixed gas with a volume ratio of 1:1 as the protective gas, and heat to 1450 - 1600°C.
6. The preparation method according to claim 3, wherein In S3, the slit width of the NB nozzle is 0.295 - 0.305 mm, and the linear velocity of the rotation of the water-cooled copper roller is 2 - 30 m / s.
7. The preparation method according to claim 3, characterized in that, In S3, the thickness of the rapidly quenched alloy ribbon is between 100 - 450 μm.
8. The preparation method according to claim 7, characterized in that, The rapidly quenched alloy ribbon has a nanocrystalline structure with a grain size of 10 - 100 nm.
9. The preparation method according to claim 3, wherein The specific parameters of the ball milling process in S4 are: the ball-to-material ratio is 20:1, the rotation speed of the ball mill is 350 revolutions per minute, and the ball milling time is 2 - 7 hours.
10. The preparation method according to claim 3, characterized in that, The ratio range of nanocrystals to amorphous phase in the ball-milled alloy powder obtained in S4 is 76:1 - 83:1.
Citation Information
Patent Citations
Low-temperature high-capacity Mg-RE-Ni-based A2B-type hydrogen storage alloy and preparation method thereof
CN105671405A
Magnesium-based nano-composite hydrogen storage material with dispersively distributed catalytic phase and preparation method of material
CN107345282A
High-volume light-weight graphene catalysis rare earth aluminum magnesium based hydrogen storage material and preparation method thereof
CN108220728A
La-Y-Mg-Ni quaternary hydrogen storage alloy with high hydrogen absorption and desorption rate and preparation method thereof
CN111996429A
Fluoride-doped high-capacity Gd-Mg-Ni-based composite hydrogen storage material and preparation method thereof
CN113881880A